Credit card operations of Eastern Bank Ltd and opinion of credit cardholders about EBL’s credit card service quality - Delwar, Raisa (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.